Porous scaffolds and soft hydrogel scaffolds for soft tissue engineering - Yang, Yang (2018)
Three dimensional (3-D) porous scaffolds are valuable in tissue engineering as they can provide the micro-environment for cell adhesion, proliferation, migration and induce tissue regeneration. Collagen is regarded as the most valuable biomaterial in tissue engineering as it is the most important and abundant structural protein in the human body.